Metagenomic next-generation sequencing for Mycobacterium tuberculosis complex detection: a meta-analysis - Li, Yulian; Bian, Wentao; Wu, Shiping; Zhang, Jie; Li, Dan (Frontiers in Public Health, 2023)
Objective: Metagenomic next-generation sequencing (mNGS) has been gradually applied to the diagnosis of tuberculosis (TB) due to its rapid and highly sensitive characteristics. Despite numerous studies on this subject, their results vary significantly. Thus, the current meta-analysis was performed to assess the performance of the mNGS on tuberculosis. Methods: PubMed, Embase, Web of science, and The Cochrane Library were searched up to June 21, 2023. Studies utilizing the mNGS for tuberculosis detection were included. The risk of bias was assessed by QUADAS-2, and a meta-analysis was performed with STATA14.0 software. Results: 17 studies comprising 3205 specimens were included. The combined sensitivity and specificity of mNGS for clinical specimens were 0.